1994
DOI: 10.1002/nau.1930130510
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of bladder outlet obstruction in rabbits

Abstract: One of the primary characteristics of partial outlet obstruction secondary to BPH is an increase in bladder mass commonly referred to as bladder hypertrophy. This condition has been simulated in rabbits by the partial ligation of the catheterized urethra. Ultrasonography has been utilized in both adult and pediatric urology to visualize the bladder and diagnose specific bladder disorders. The aim of the present study is to determine if ultrasonography can visualize bladder wall hypertrophy induced by obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Schoor et al [1994] ¢rst demonstrated in rabbits that bladder wall thickness can be measured with an ultrasound device accurately. Later, other study groups used ultrasound technology in men with BPH [Kojima et al, 1996[Kojima et al, , 1997Manieri et al, 1998;Hakenberg et al, 2000;Oelke et al, 2002] and in children with non-neurogenic bladder dysfunction [Cvitkovic-Kuzmic et al, 2002] to prove thickening of the bladder wall due to BOO as well as in women to discriminate between stress and urge urinary incontinence [Khullar et al, 1994[Khullar et al, , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Schoor et al [1994] ¢rst demonstrated in rabbits that bladder wall thickness can be measured with an ultrasound device accurately. Later, other study groups used ultrasound technology in men with BPH [Kojima et al, 1996[Kojima et al, , 1997Manieri et al, 1998;Hakenberg et al, 2000;Oelke et al, 2002] and in children with non-neurogenic bladder dysfunction [Cvitkovic-Kuzmic et al, 2002] to prove thickening of the bladder wall due to BOO as well as in women to discriminate between stress and urge urinary incontinence [Khullar et al, 1994[Khullar et al, , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…18 It was hypothesized that detrusor wall thickness (DWT) or bladder wall thickness (BWT) reflects the workload of the bladder similar to the heart, in which the cardiac wall thickens in patients affected by arterial hypertension or cardiac valve stenosis. 19 Bladder wall hypertrophy can be imaged with ultrasound technology in experimental animals with partial BOO 20 and humans with neurogenic or nonneurogenic bladder dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…1 Additionally, about 28% of men over 70 years old have moderate-tosevere lower urinary tract symptoms (LUTS). 2,3 Bladder outflow obstruction (BOO) is found in 60% of symptomatic patients, and in 52% of asymptomatic patients.…”
Section: Introductionmentioning
confidence: 99%